Sejarah Pemikiran Ekonomi Islam: Aktifitas Perbankan pada Rasulullah dan Masa Khulafa Al-Rasyidin - Batubara, Maryam; Ivanka, Meitia; Ningsih, Nur Widya; Nasution, Silvia Zahra; Sitompul, Gandhi Sulaiman (Ikatan Da'i Indonesia, 2024)
Islamic Economic Thought during the Khulafaurrasyidin period. The method used is library research using several books as a source of writing. In the beginning, Islamic economics was practiced by Rasulullah SAW in trade activities and also in implementing the fiscal and monetary policies of the Islamic State. After Rasulullah SAW died, the leadership of the Islamic State and also the management of the economy were then continued by Khulafaurrasyidin. The economy during the time of Abu Bakar Ash Shidiq was colored by the rebellion of apostates who were not willing to pay zakat. During the time of Umar bin Khattab, the treasures of the baitul mal were left for reserve funds. At the end of Uthman bin Affan's reign, there was political turmoil due to allegations of corrupt officials. In the era of Ali bin Abi Talib, the Islamic State minted coins on behalf of the Islamic State.